Adaptability as a predictor of psychological well-being personality (Actual Problems of Psychology in Educational Institutions, 2018)
The article analyzes the theoretical foundations of the problem of psychological well-being and personality adaptability. The basic parameters of these phenomena are determined, their connection is shown. It has been established that the person's adaptability is expressed in her satisfaction with life, in mental and emotional equilibrium, in the adequacy of her behavior to social requirements and congruence to inner values and desires. The prognostic role of person's adaptability in relation to her psychological well-being is substantiated.
Keywords: psychological well-being; adaptability; positive functioning; satisfaction; capacity for adjustments